Sulfotransferase activity in plucked hair follicles predicts response to topical minoxidil in the treatment of female androgenetic alopecia. Issue 4 (28th April 2014) - Roberts, Janet; Desai, Nisha; McCoy, John; Goren, Andy
Abstract Two percent topical minoxidil is the only US Food and Drug Administration‐approved drug for the treatment of female androgenetic alopecia (AGA). Its success has been limited by the low percentage of responders. Meta‐analysis of several studies reporting the number of responders to 2% minoxidil monotherapy indicates moderate hair regrowth in only 13–20% of female patients. Five percent minoxidil solution, when used off‐label, may increase the percentage of responders to as much as 40%. As such, a biomarker for predicting treatment response would have significant clinical utility. In a previous study, Goren et al. reported an association between sulfotransferase activity in plucked hair follicles and minoxidil response in a mixed cohort of male and female patients. The aim of this study was to replicate these findings in a well‐defined cohort of female patients with AGA treated with 5% minoxidil daily for a period of 6 months. Consistent with the prior study, we found that sulfotransferase activity in plucked hair follicles predicts treatment response with 93% sensitivity and 83% specificity. Our study further supports the importance of minoxidil sulfation in eliciting a therapeutic response and provides further insight into novel targets for increasing minoxidil efficacy.